PENGARUH PENGETAHUAN DAN SIKAP TERHADAP PARTISIPASI MASYARAKAT PADA PENGELOLAAN BANK SAMPAH DI KECAMATAN BATU AJI – KOTA BATAM: Timbul Dompak dan Nikita Simarmata - Dialektika Publik (Dialektika Publik, 2017)
This study aims to determine the effect of Knowledge (X1) and Attitude (X2) on Community Participation in Waste Bank Management (Y) in Batu Aji Sub-district, Batam City. This study uses a quantitative approach by distributing questionnaires to the garbage bank management unit located in Batu Aji district. This study used a saturated sample of 38 respondents. Data analysis used is multiple linear regression. The conclusions of the results of this study indicate that: (1). Partially that Knowledge influence to Community Participation in Waste Bank Management (t count = 5,736 > t table = 2,030); (2). Partially that Attitudes not affect Community Participation in Waste Bank Management (t count = 1.176 < t table = 2,030); (3). Simultaneously Knowledge and Attitudes significantly influence the Community Participation in Waste Management Bank (F count = 16.666> F table =3.27)